Alpha-lipoic acid prevents side effects of therapeutic nanosilver without compromising cytotoxicity in experimental pancreatic cancer - An, Xuefeng; Liu, Li; Schäfer, Michael; Yan, Bin; Scholz, Christian; Hillmer, Stefan; Wang, Kangtao; Luo, Yiqiao; Ji, Huihui; Gladkich, Jury; Herr, Ingrid (Cancers, 2021)
Silver nanoparticles (AgNPs) have attracted attention in cancer therapy and might support the treatment of pancreatic ductal adenocarcinoma (PDAC). Silver is in clinical use in wound dressings, catheters, stents and implants. However, the side effects of systemic AgNP treatment due to silver accumulation limit its therapeutic application. We evaluated whether the antioxidant and natural agent α-lipoic acid might prevent these side effects. We synthesized AgNPs using an Ionic-Pulser® Pro silver generator and determined the concentration by inductively coupled plasma-optical emission spectrometry. The effect of α-lipoic acid was examined in four PDAC and two nonmalignant cell lines by MTT, FACS analysis, TEM, xenotransplantation and immunohistochemistry. The viability of PDAC cells was nearly totally abolished by AgNP treatment, whereas nonmalignant cells largely resisted. α-Lipoic acid prevented AgNP-induced cytotoxicity in nonmalignant cells but not in PDAC cells, which might be due to the higher sensitivity of malignant cells to silver-induced cytotoxicity. α-Lipoic acid protected mitochondria from AgNP-induced damage and led to precipitation of AgNPs. AgNPs reduced the growth of tumor xenografts, and cotreatment with α-lipoic acid protected chick embryos from AgNP-induced liver damage. Together, α-lipoic acid strongly reduced AgNP-induced side effects without weakening the therapeutic efficacy.